Impact of foreign aid on income inequality in emerging markets - Tsaurai, Kunofiwa (Acta Universitatis Danubius. Œconomica, 2023)
This paper investigated the influence of foreign aid on income inequality in selected emerging markets using panel data (2004-2019) analysis methods such as fully modified ordinary least squares (FMOLS), fixed effects and pooled ordinary least squares (OLS). The study also examined whether human capital development is a channel through which foreign aid influenced income inequality or whether human capital development is one of the conditions which must be fulfilled in the recipient country before foreign aid can have a significant reduction effect on income inequality in selected emerging markets. Foreign aid was found to have non-significantly reduced income inequality across all the three estimation methods. Pooled OLS and FMOLS show that human capital development significantly reduced income inequality. Under the fixed effects and FMOLS, human capital development was found to be a factor which be available in the recipient country before foreign aid can significantly reduce income inequality in selected emerging markets. Foreign direct investment and unemployment significantly led to the increase in income inequality across all the three econometric estimation methodologies. Trade openness and financial development produced similar results but only under the pooled OLS. Trade openness significantly reduced income inequality under the FMOLS and the fixed effects. Responsible authorities are therefore urged to implement policies that increases human capital development, financial development and trade openness to enhance income inequality reduction in selected emerging markets.